Promoting Disability-Friendly Campuses to Prospective Students: An Analysis of University Recruitment Materials - Haller, Beth A. (Disability Studies Quarterly, 2006)
Estimates are that currently about 9 percent of students on college campuses have some form of disability. These students are all are supposed to receive accommodations on those college campuses based on Section 504 of the Rehabilitation Act and the Americans with Disabilities Act. The focus of this study is how these students receive information about these accommodations, their rights, the campus accessibility, and other issues related to them. The findings of this study show that university viewbooks and other materials sent to interested high school students are depicting disability. However, there does not appear to be much recruitment of prospective students with disabilities past the occasional picture in the viewbook. No cover letter made a mention of unique services for students with disabilities, and less than half of the university general materials mentioned campus disability services (40%). In addition, only 39 percent of the schools that sent any general materials sent Disabled Student Services (DSS) materials (N=85).